Macrophages Orchestrate Hematopoietic Programs and Regulate HSC Function During Inflammatory Stress - Seyfried, Allison N.; Maloney, Jackson M.; MacNamara, Katherine C. (Frontiers in Immunology, 2020)
The bone marrow contains distinct cell types that work in coordination to generate blood and immune cells, and it is the primary residence of hematopoietic stem cells (HSCs) and more committed multipotent progenitors (MPPs). Even at homeostasis the bone marrow is a dynamic environment where billions of cells are generated daily to replenish short-lived immune cells and produce the blood factors and cells essential for hemostasis and oxygenation. In response to injury or infection, the marrow rapidly adapts to produce specific cell types that are in high demand revealing key insight to the inflammatory nature of “demand-adapted” hematopoiesis. Here we focus on the role that resident and monocyte-derived macrophages play in driving these hematopoietic programs and how macrophages impact HSCs and downstream MPPs. Macrophages are exquisite sensors of inflammation and possess the capacity to adapt to the environment, both promoting and restraining inflammation. Thus, macrophages hold great potential for manipulating hematopoietic output and as potential therapeutic targets in a variety of disease states where macrophage dysfunction contributes to or is necessary for disease. We highlight essential features of bone marrow macrophages and discuss open questions regarding macrophage function, their role in orchestrating demand-adapted hematopoiesis, and mechanisms whereby they regulate HSC function.